The role of prominence in determining the scope of boundary-related lengthening in Greek. (March 2016) - Katsika, Argyro
Abstract: This study aims at examining and accounting for the scope of the temporal effect of phrase boundaries. Previous research has indicated that there is an interaction between boundary-related lengthening and prominence such that the former extends towards the nearby prominent syllable. However, it is unclear whether this interaction is due to lexical stress and/or phrasal prominence (marked by pitch accent) and how far towards the prominent syllable the effect extends. Here, we use an electromagnetic articulography (EMA) study of Greek to examine the scope of boundary-related lengthening as a function of lexical stress and pitch accent separately. Boundaries are elicited by the means of a variety of syntactic constructions. The results show an effect of lexical stress. Phrase-final lengthening affects the articulatory gestures of the phrase-final syllable that are immediately adjacent to the boundary in words with final stress, but is initiated earlier within phrase-final words with non-final stress. Similarly, the articulatory configurations during inter-phrasal pauses reach their point of achievement later in words with final stress than in words with non-final stress. These effects of stress hold regardless of whether the phrase-final word is accented or de-accented. Phrase-initial lengthening, on the other hand, is consistently detected on the phrase-initial constriction, independently of where the stress is within the preceding, phrase-final, word. These results indicate that the lexical aspect of prominence plays a role in determining the scope of boundary-related lengthening in Greek. Based on these results, a gestural account of prosodic boundaries in Greek is proposed in which lexical and phrasal prosody interact in a systematic and coordinated fashion. The cross-linguistic dimensions of this account and its implications for prosodic structure are discussed. Highlights: Lexical stress affects the initiation of phrase-final lengthening. Pitch accent does not affect the scope of phrase-final lengthening. Lexical stress affects the duration of pause posture formation. Lexical stress affects the distribution of boundary-related shortening. The domain of boundary-related lengthening is continuous.